COVID-19 vaccine allergy advice and guidance: The experience of a UK tertiary referral centre - Moghaddas, Fiona; Tsiougkos, Nikolaos; Grammatikos, Alexandros; Bright, Philip D.; Johnston, Sarah; Gompels, Mark (The World Allergy Organization journal, 2023)
The objective was to review COVID-19 vaccine allergy advice and guidance requests received and assess the impact of advice outcome on vaccination outcome. A retrospective analysis of requests for advice and guidance regarding COVID-19 vaccine allergy was completed using an electronic referral system from February 2021 to January 2022. A total of 1265 independent patient requests for advice were received from primary care. Full vaccination information was available on 1210 patients who were included in the analysis. We evaluated the specific outcome of request for advice (written advice versus allergy consultation), rate of vaccination, vaccination combinations, and tolerance of vaccination. Of the 1210 patients included, 959 (79%) were female. Eight hundred and ninety-six (74%) requests were managed with written advice only and of these 675 (75%) patients went on to be vaccinated. Overall, 891 (74%) of the population were vaccinated with 2 or more doses. Two hundred and nineteen patient consultations were undertaken with 109 (50%) prior to the first vaccination. Forty-nine (45%) consultations prior to vaccination were undertaken due to a label of anaphylaxis to vaccination in the past. Vaccination was recommended for all patients, and 78 (72%) of these received a first dose. Eight of these patients (10%) had symptoms within 1 h of vaccine administration. One hundred and ten (50%) consultations were undertaken for adverse reactions post COVID-19 vaccination, with 84 (76%) concerning immediate symptoms. Thirty patients (27%) who had a consultation had had adrenaline administered post vaccination. One patient had biopsy confirmed Stevens Johnson Syndrome and was referred to Dermatology. All others due for further doses (107 patients) were recommended to have subsequent doses with 49 (45%) offered the same vaccine. Eighty-nine patients had a vaccine administered post adverse reaction and 79 (88%) tolerated the dose. Skin testing and challenge to polyethylene glycol were negative in the 8 patients tested. Over 1000 requests for advice and guidance were received during the review period, managed mainly with written advice. The overwhelming majority of requests for advice and consultations were for females, with equal distribution both pre- and post-COVID-19 vaccine administration. Vaccination was recommended in all but 1 patient (with biopsy confirmed Stevens Johnson Syndrome). Polyethylene glycol allergy was not confirmed in any patient, nor did any patient have confirmed anaphylaxis when the vaccine was administered under our supervision, suggesting that type 1 mediated hypersensitivity is uncommon even in this "high risk" population.